A STUDY OF URBAN WATER DEMAND IN SOUTH KALIMANTAN PROVINCE - Ulfa Fitriati; Novitasari Novitasari; Muh. Afief Ma’ruf (TROPICAL WETLAND JOURNAL, 2017)
This research projected the citizens and water demand in 13 regencies/cities in South Kalimantan Province from 2013 to the next 20 years. The results of the project were compared with the intake capacity to meet the demand in upcoming years. In projecting the population growth, five methods were used, namely aritmethic method, geometric method, linier regression method, exponential method and logarithmic method. The most appropriate method for projecting the population growth is the method which has the minimum value of standard deviation and the correlation value close to 1. Water demand was calculated based on some factors, such as the average water demand, the maximum level of water demand, and the water demand at peak hours. The existing intake capacity was then compared with the water demand projection. In almost all PDAM (Munipical Tap Water Company) observed, the capacity of water processing installation could not fullfill the water demand at the peak hours. The adequate intake capacity of PDAM was only in Balangan regency and Banjarmasin city.